2020
DOI: 10.1007/s12662-020-00677-4
|View full text |Cite
|
Sign up to set email alerts
|

The relative age effect in German 11- to 18-year-old male and female swimmers

Abstract: Relatively older athletes have a greater probability of being selected and subsequently exposed to a higher level of coaching, training and other talent-promoting factors. Grouping by chronological age is, therefore, considered to be one of the weaknesses in talent identification. A large number of studies have confirmed the prevalence of the relative age effect (RAE) across various sports, including swimming. This investigation aims to quantify the prevalence, magnitude and transient pattern of the RAE accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 42 publications
1
4
2
5
Order By: Relevance
“…In the present study, the prevalence of the RAE seemed to decline with age, and there was a clear effect between the ages of 12 and 14 years in both male and female swimmers [26,[50][51][52]. After that, the influence of the RAE seemed to fade away, especially around the ages of 17-18 years, before completely disappearing in elite competition [48].…”
Section: Prevalence Of the Rae According To Constraints-based Modelsupporting
confidence: 43%
See 3 more Smart Citations
“…In the present study, the prevalence of the RAE seemed to decline with age, and there was a clear effect between the ages of 12 and 14 years in both male and female swimmers [26,[50][51][52]. After that, the influence of the RAE seemed to fade away, especially around the ages of 17-18 years, before completely disappearing in elite competition [48].…”
Section: Prevalence Of the Rae According To Constraints-based Modelsupporting
confidence: 43%
“…Of the six studies analysed, four studies included a mixed sample in terms of gender [47][48][49][50], while the other two were composed of only men [51] or women [52]. All the studies were focused on formative categories (11-18 years) and national competitions, except the one carried out by Ferreira et al [48], which was found to be made up of a senior sample that participated in an international competition (i.e., Olympic Games).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Con relación a la natación, deporte objeto de estudio en esta investigación, el contexto cultural se ha mostrado como moderador del RAE, siendo los resultados heterogéneos en función del país de estudio, tanto en el grado, periodo de mayor incidencia y persistencia en el tiempo (Staub, Stallman & Vogt, 2020). Con relación a las demandas propias de la natación, el RAE podría verse moderado por las demandas propias de cada estilo y la distancia de la prueba (Silva et al, 2007;Costa, Marques, Louro, Ferreira & Marinho, 2013;Staub et al, 2020). Hasta hace muy pocos años, la natación no ha tenido gran consideración en la investigación del RAE (Smith, Weir, Till, Romann & Cobley, 2018), no conociéndose estudios en el contexto español.…”
unclassified